Strengthening The Integrated Steam Of Technologies In The Environment Of Information Technologies And Computer Programs (Texas Journal of Engineering and Technology, 2022)
This article reveals the aspects of strengthening integrated learning in the content of STEAM learning technology by means of information technology and computer programs. The author submits the idea of earlier teaching computer science, teaching children, together with their parents, programming in the Scratch program and in the Python programming language based on different methods, divided by age and intellectual characteristics of children, i.e. here we are talking about the training program for preschoolers, school students and finally graduate students, who will teach computer science and information technology in the future. Preference will also be given to additional education, circle lessons aimed at teaching and learning subjects in the style of STEAM technologies in continuous areas of education